Analysis and synthesis of images of environmentally oriented innovative technologies of construction production - V. I. Telichenko; A. A. Lapidus; M. Yu. Slesarev (Vestnik MGSU)
Introduction. Is automated generation of technological inventions possible or not? To test this hypothesis, the authors propose to test the integration of human machine and living intelligence using artificial intelligence, using the example of the GPT neural network developed by Microsoft and OpenAI.Materials and methods. The use of artificial intelligence in the creative synthesis of environmentally oriented progressive or perspective verbal and graphic images of breakthrough technologies, taking into account the statistical processing of patent information and funds of technical regulations is one of the tasks of creative forecasting of technosphere objects.Results. The purpose of the study has been achieved – approaches to the development of methods of automated forecasting of breakthrough technologies of construction production have been outlined. The following research tasks were solved: search for methods of researching the future of the construction industry; search for correct terminology for synthesizing images of future breakthrough technologies and options for using artificial intelligence capable of creatively generating verbal and graphic images of technologies. The object of research — aspects of automated prediction of promising construction technologies is confirmed. The subject of the study — verbal and graphic images of future breakthrough technologies of environmentally oriented construction production is confirmed.Conclusions. The review of images of breakthrough technologies of construction production showed the possibility of integrating live and artificial intelligence with appropriate terminological and methodological elaboration of databases and information logistics algorithms for automated generation of new technological inventions. The use of artificial intelligence in the creative synthesis of environmentally oriented verbal and graphic images of breakthrough technologies, taking into account the statistical processing of patent information and funds of technical regulations, is one of the tasks of creative forecasting of technosphere objects.